ANALISIS KINERJA TIM PERCEPATAN PENURUNAN STUNTING DI KABUPATEN MURUNG RAYA - Daniel Patandianan (STKIP Persada Khatulistiwa Sintang, 2025)
Stunting is a major public health issue in Indonesia, affecting children's cognitive development, educational achievements, and future productivity. This study aims to analyze the relationship between competence, work motivation, and performance of the Stunting Reduction Acceleration Team (TPPS) in Murung Raya Regency. Using a quantitative method and explanatory research approach, data were collected via a survey of 63 respondents from various roles within the TPPS. The Partial Least Square (PLS) method was used for model testing. The results reveal that competence does not directly influence TPPS performance but significantly impacts work motivation. Work motivation, in turn, directly affects TPPS performance significantly. Furthermore, work motivation serves as a moderating variable that strengthens the relationship between competence and performance. These findings underscore the importance of enhancing work motivation as a strategic measure to maximize the impact of competence on performance. Thus, the study recommends motivation-based training to improve TPPS performance in sustainable stunting reduction efforts. This finding emphasizes the importance of a holistic approach in managing human resources, where increasing competence must be accompanied by efforts to foster work motivation to achieve optimal performance